Habitualization of Pesantren Values as Social Capital in Building Moderate Islamic Education - Fauzi, Ahmad; Suheri; Fermadi, Bayu (Cendekia: Kependidikan dan Kemasyarakatan, 2024)
This research aims to interpret the value system built by pesantren and its existence as social capital. It is believed to inspire, influence, and mobilize individual social actions and behavior in society. Thus, this research employed a qualitative approach through Pierre Bourdieu’s social practice theory regarding practice (action and behavior) as the outcome of the interaction between an individual’s habitus and available capital within a specific domain/field. It produces a grounded theory to provide a holistic and comprehensive understanding. This research practically shows some findings. First, pesantren values ”‹”‹result from creating creative individuals based on the logic of thought and scientific genealogy of kiai based on their understanding of various Islamic texts, which then inspire the formation of a value system. Second, the existence of these values ”‹”‹is made into a shared belief and transmitted within the pesantren institution so that, in the end, it becomes part of the pesantren tradition. Third, the habitualization of pesantren values ”‹”‹is understood as social capital and can be used as a core value in building a moderate Islamic education model. So, it then shapes the character or attitude of tawassuth, tawÄzun, tasÄmuh, tahadhdhur, musÄwah, i'tidÄl, al-IslÄh, tathawur wa IbtikÄr, and shurÄ, according to the typology of each pesantren.